Mechanical against chemical pressure in the Y(Ba1-xSrx)(2)Cu3O7-d system - Marezio, M; Gilioli, E; Radaelli, P; Gauzzi, A; Licci, F (2000)
The structural refinement of YSr2Cu3O6.84 allows us to analyze why the chemical pressure applied to YBa2Cu3O6.84, by substituting Sr for Ba, results in a decrease of Tc (88 to 63 K). Even though the chemical pressure induces a volume decrease of 5.7%, the thickness along the c axis of the superconducting block increases by 3.0%. This behavior seems to be due to the incompressibility of the Y coordination polyhedron. The SrO layer becomes negatively strained since the Sr polyhedron does not reduce along with the Sr cation substitution. The calculated bond valence sum for the latter cation is 1.63 v.u. instead of the expected 2. The apical distance of the pyramid around Cu2 decreases drastically from 2.30 to 2.09 Å. All these features induce an instability within YSr2Cu3O6.84, which makes it difficult for the extra oxygen to go in and out of the structure as it does in its Ba counterpart. This instability would also reduce the hole transfer from the CuO chains to the superconducting CuO2 planes. © 2000 Elsevier Science B.V All rights reserved.